EFFECT OF PRUDENTIAL GUIDELINES ON THE FINANCIAL PERFORMANCE OF DEPOSIT MONEY BANKS IN NIGERIA (Journal of Global Accounting, 2023)
This study examined the effect of prudential guidelines on the financial performance of deposit money banks in Nigeria. The specific objective of the study were to: examine the impact of capital adequacy regulation on the financial performance of DMBs in Nigeria; ascertain the impact of liquidity regulation on the financial performance of DMBs in Nigeria and assess the impact of credit risk regulation on the financial performance of DMBs in Nigeria. The study was anchored on agency and liquidity preference theories. The study adopt multivariate regression estimation analysis, correlation analysis and descriptive statistics. The study used Capital Adequacy Regulation (CAR), Liquidity Regulation (LR) and Credit Risk Regulation (CRR) as a proxy for Prudential Guideline and Return on Asset (ROA) and Return on Equity (ROE) as a measure for Financial Performance. The result show that CAR has a negative but insignificant effect on ROA, but has a positive and significant effect on DMBs' ROE in Nigeria. LR is negatively correlated with DMBs financial performance in Nigeria. CRR has a detrimental negative effect on DMBs' financial performance in Nigeria. The study recommended among other things that the minimum capital requirement of DMBs in Nigeria should be reviewed on a regular basis to ensure that it remains at an optimal level, and Nigerian banks should be capitalized to enable them to access cheaper sources of funds, resulting in increased profit margins. This would go a great way toward restoring public trust in banks, as the latter would be better equipped to provide consumers' credit demands while also safeguarding depositors' funds.
Keywords: Capital adequacy regulation; Credit risk regulation; Liquidity regulation; Prudential guideline